Intersections of food insecurity, violence, poor mental health and substance use among US women living with and at risk for HIV: Evidence of a syndemic in need of attention - Leddy, Anna M.; Zakaras, Jennifer M.; Shieh, Jacqueline; Conroy, Amy A.; Ofotokun, Ighovwerha; Tien, Phyllis C.; Weiser, Sheri D. (PLOS ONE, 2021)
Background Food insecurity and intimate partner violence (IPV) are associated with suboptimal HIV prevention and treatment outcomes, yet limited research has explored how food insecurity and IPV intersect to influence HIV-related behaviors. To fill this gap, we conducted a qualitative study with women living with or at risk for HIV in the United States. Methods We conducted 24 in-depth interviews with women enrolled in the San Francisco and Atlanta sites of the Women’s Interagency HIV study (WIHS). Participants were purposively sampled so half were living with HIV and all reported food insecurity and IPV in the past year. Semi-structured interviews explored experiences with food insecurity and IPV, how these experiences might be related and influence HIV risk and treatment behaviors. Analysis was guided by an inductive-deductive approach. Results A predominant theme centered on how food insecurity and IPV co-occur with poor mental health and substance use to influence HIV-related behaviors. Women described how intersecting experiences of food insecurity and IPV negatively affected their mental health, with many indicating using substances to “feel no pain”. Substance use, in turn, was described to perpetuate food insecurity, IPV, and poor mental health in a vicious cycle, ultimately facilitating HIV risk behaviors and preventing HIV treatment adherence. Conclusions Food insecurity, IPV, poor mental health and substance use intersect and negatively influence HIV prevention and treatment behaviors. Findings offer preliminary evidence of a syndemic that goes beyond the more widely studied “SAVA” (substance use, AIDS, and violence) syndemic, drawing attention to additional constructs of mental health and food insecurity. Quantitative research must further characterize the extent and size of this syndemic. Policies that address the social and structural drivers of this syndemic, including multi-level and trauma-informed approaches, should be implemented and evaluated to assess their impact on this syndemic and its negative health effects.